Nitrogen recovery, use efficiency, dry matter yield, and chemical composition of palisade grass fertilized with nitrogen sources in the cerrado biome - Dupas, Elisângela [UNESP]; Buzetti, Salatiér [UNESP]; Silveira Rabêlo, Flávio Henrique; Sarto, André Luís; Cheng, Nicole Colombari; Minhoto Teixeira Filho, Marcelo Carvalho [UNESP]; Galindo, Fernando Shintate [UNESP]; Dinalli, Raíssa Perreira [UNESP]; de Niro Gazola, Rodolfo [UNESP] (Southern Cross Publishing, 2016)
The high cost and the low efficiency of fertilizers, especially nitrogen (N), are of major concerns in agriculture. This study aimed to evaluate the effect of N fertilizers sources in Urochloa brizantha cv. Marandu (palisade grass). The study was conducted in Cerrado of Brazil to evaluate dry-matter yield (DMY), recovery of applied N (RAN), N use efficiency (NUE), and chemical composition of palisade grass in response to sources of N (ammonium nitrate, ammonium sulfate, ammonium sulfate-nitrate, urea, urea with urease inhibitor, polymer-coated urea, and control) in seven harvests (100 kg ha-1 N were applied after each harvest). The N fertilization increased DMY and growth of palisade grass compared to control (without N fertilization). However, there was not any difference in DMY due to N sources. Application of ammonium sulfate-nitrate increased RAN. The urea, urea with urease inhibitor, and polymer-coated urea improved NUE. Concentration of neutral detergent fiber (NDF) was decreased, while concentrations of acid detergent fiber (ADF) and cellulose were not affected by the fertilizers. Crude protein (CP) content was increased with N supply, but CP fractions A and B were not changed, except in the fifth period of growth. The results indicated protected fertilizers (ammonium sulfate-nitrate, urea with urease inhibitor, and polymer-coated urea) are more recommended for the cultivation of palisade grass in the Cerrado biome of Brazil.
Keywords: Cell wall; Crude protein fractionation; Lignin; Protected fertilizers; Urochloa brizantha